Variation in Left Ventricular Assist Device Postdischarge Caregiver Requirements: Results From a Mixed-Methods Study With Equity Implications. (7th July 2022) - Knoepke, Christopher E.; Siry-Bove, Bonnie; Mayton, Caitlin; Latimer, Abigail; Hart, Jan; Allen, Larry A.; Daugherty, Stacie L.; McIlvennan, Colleen K.; Matlock, Daniel D.; Khazanie, Prateeti
Abstract : Background: Left ventricular assist device (LVAD) evaluation includes a psychosocial assessment, conducted by social workers (SWs) on the advanced heart failure multidisciplinary team. Postdischarge caregiving plans are central to psychosocial evaluation. Caregiving's relationship with LVAD outcomes is mixed, and testing patients' social resources may disadvantage those from historically undertreated groups. We describe variation in policies defining adequate caregiving plans post-LVAD implant and possible impacts on patients from marginalized groups. Methods: This was a 2-phase sequential mixed-methods study: (1) phase 1, survey of US-based LVAD SWs, describing assessment structure and policies guiding candidacy outcomes; and (2) phase 2, individual interviews with SWs to further describe how caregiving plan adequacy impacts LVAD candidacy. Results: Sixty-seven SWs returned surveys (rr=47%) from unique programs. Caregiving plan inadequacy (n=30) was the most common psychosocial dealbreaker. When asked what duration of caregiving is required, 23% indicated ≥3 months, 27% 4 to 12 weeks, and 30% <4 weeks. Two reported no duration requirement, 6 stated an indefinite 24/7 commitment was necessary. Across 22 interviews, SWs mirrored that caregiving plans were the most common psychosocial contraindication. How caregiving is operationalized varied. Participants voiced a tension between extended caregiving improving outcomes and the sense that some people of color, women, or low socioeconomic status patients struggle to meet stringent requirements. Conclusions: Policies regarding adequate duration of 24/7 caregiving vary, but inadequate caregiving plans are the most common psychosocial contraindication. Participants worry about patients' ability to meet restrictive requirements, particularly from historically undertreated groups. This highlights a need to operationalize quality caregiving, standardize assessment, and support medically appropriate patients with strained social resources.